‘The witness is lying!’: the impact of a defendant countering a jailhouse informant’s testimony - Wetmore, Stacy A. (Psychology, crime & law, 2023)
The present study investigated the impact of a defendant explicitly countering the claim of a jailhouse informant that the defendant confessed to a murder. Jury-eligible community members (N = 127) recruited from Amazon’s Mechanical Turk read (via Qualtrics) a fictional trial summary in which a defendant was accused of murder. The trial was presented in one of four conditions: jailhouse informant only, defendant explicitly countered the jailhouse informant’s testimony (said he did not talk to the jailhouse informant or they talked but not about the case), defendant testified but did not explicitly counter the jailhouse informant’s testimony (simply said he was innocent), and no jailhouse informant testimony. As predicted, when the defendant explicitly countered the jailhouse informant’s testimony the number of guilty verdicts was lower than that when the jailhouse informant only testified. In addition, there was significant mediation, such that explicitly countering the jailhouse informant led to lower jailhouse informant credibility and fewer guilty verdicts. Finally, cognitive network analyses showed that countering the jailhouse informant’s testimony was critical to participants representing the jailhouse informant’s testimony in a negative light. We discuss these results in terms of the importance of countering what is often unreliable jailhouse informant testimony.